The effects of dry-rolled corn particle size on performance, carcass traits, and starch digestibility in feedlot finishing diets containing wet distiller's grains - Schwandt, E. F.; Wagner, J. J.; Engle, T. E.; Bartle, S. J.; Thomson, Daniel U.; Reinhardt, Christopher D. (My University, 2016)
Crossbred yearling steers (n = 360; 395 +/- 33.1 kg initial BW) were used to evaluate the effects of dry-rolled corn (DRC) particle size in diets containing 20% wet distiller's grains plus solubles on feedlot performance, carcass characteristics, and starch digestibility. Steers were used in a randomized complete block design and allocated to 36 pens (9 pens/treatment, with 10 animals/pen). Treatments were coarse DRC (4,882 mu m), medium DRC (3,760 mu m), fine DRC (2,359 mu m), and steam-flaked corn (0.35 kg/L; SFC). Final BW and ADG were not affected by treatment (P > 0.05). Dry matter intake was greater and G:F was lower (P < 0.05) for steers fed DRC vs. steers fed SFC. There was a linear decrease (P < 0.05) in DMI in the final 5 wk on feed with decreasing DRC particle size. Fecal starch decreased (linear, P < 0.01) as DRC particle size decreased. In situ starch disappearance was lower for DRC vs. SFC (P < 0.05) and linearly increased (P < 0.05) with decreasing particle size at 8 and 24 h. Reducing DRC particle size did not influence growth performance but increased starch digestion and influenced DMI of cattle on finishing diets. No differences (P > 0.10) were observed among treatments for any of the carcass traits measured. Results indicate improved ruminal starch digestibility, reduced fecal starch concentration, and reduced DMI with decreasing DRC particle size in feedlot diets containing 20% wet distiller's grains on a DM basis.
Citation: Schwandt, E. F., Wagner, J. J., Engle, T. E., Bartle, S. J., Thomson, D. U., & Reinhardt, C. D. (2016). The effects of dry-rolled corn particle size on performance, carcass traits, and starch digestibility in feedlot finishing diets containing wet distiller's grains. Journal of Animal Science, 94(3), 1194-1202. doi:10.2527/jas2015-9408
Keywords: Dry Rolled Corn; Fecal Starch; Feedlot; Particle Size; By-Products; Digestion